Graphene Modifications in Polylactic Acid Nanocomposites: A Review - Kamal, Yusoh; Norazlina, H. (Springer Berlin Heidelberg, 2015)
Considerable interest has been devoted to graphene since this material has shown promising and excellent results in mechanical and thermal properties. This finding has attracted more researchers to discover the attributes of graphene due to its extensive and potential applications. This paper reviewed the recent advances in the modification of graphene and the fabrication of polylactic acid/graphene nanocomposite. The different techniques that have been employed to prepare graphene, such as reduction of graphene oxide and chemical vapor deposition, are discussed briefly. The preparations of PLA/graphene nanocomposites are described using in situ polymerization, solution, and melt blending; and the properties of these nanocomposites are reviewed. Due to the difficulties in obtaining good dispersions, modifications of nanomaterials have been the critical issues that lead to excellent mechanical properties.